Recent hemispheric asymmetry in global ocean warming induced by climate change and internal variability - Saurabh Rathore (Nature Portfolio, 2020)
Observations of global ocean heat content during 2005–2015 have shown a strong hemispheric asymmetry, and the southern hemisphere accounts 92% of the total heat gain. Here, the authors show that the rate of observed global ocean warming is consistent with a forced symmetric climate change signal and an asymmetric climate variation for this period.